Factors Influencing the use of Long-Term Contraceptive Methods in Adult Women - Sahputra, Rahmat Tridhandy; Sari, Ratna Dewi Puspita; Utama, Winda Trijayanthi (Global Health Science Group, 2025)
The world's population has increased many times over the last 200 years, so that the number is now recorded at more than seven billion people. The size of the population is not evenly distributed, therefore it is necessary to have something that can prevent population spikes. Family Planning Policy aims to control population growth through efforts to reduce the birth rate. Many women have difficulty in choosing the type of contraception. This is not only due to the limited availability of methods, but also due to ignorance about the requirements and safety of these contraceptive methods. The purpose of this study was to analyze the factors that influence women to choose the long-term contraceptive method. The design of this study used an analytic observational type with a cross sectional approach. The sampling technique is Consecutive sampling. The number of samples in this study were 60 women of childbearing age who used the long-term contraceptive method and 60 women of childbearing age who used the long-term contraceptive method.Results: The results showed that Age had a P-Value of 0.714, Education had a P-Value of 0.004, Employment had a P-Value of 0.711, Knowledge had a P-Value of 0.015, Number of children had a P-Value of 0.030, Attitudes had a P-Value of 0.037, Role Health Workers have a P-Value of 0.027, Husband's Support has a P-Value of 0.031, Social Culture has a P-Value of 0.032. The conclusion in this study is that there is an influence of Education, Knowledge, Number of Children, Attitudes, Role of Health Workers, Husband's Support and Socio-cultural Affairs on the selection of the long-term contraceptive method, while Age and Occupation have no influence in choosing the long-term contraceptive method.